Relationship of Student Learning Creativity With SBdP Learning Outcomes Grade Iv Sd Gpid Palu - Erlis Erlis; Yun Ratna Lagandesa (JURNAL BANUA OGE TADULAKO, 2022)
The purpose of this study is to find out the relationship of student learning creativity with the learning outcomes of SBdP Class IV SD GPID Palu. The hypothesis tested in this study is "There is a Relationship of Siawa Learning Creativity with SBdP Learning Outcomes Grade IV SD GPID Palu". The subjects taken are class IV as many as 30 students to collect data, used instruments in the form of questionnaires given to grade IV students and see the results of raport grades. Furthermore, the collected data is processed and analyzed using the technique of percentage and correlation of product moment at the level of 95% confidence. The results of this study showed that 25 students or 83.33% of students think learning creativity is very high, 5 students or 16.66% of students think learning creativity is relatively high, and there are no students or 0% of students who think learning creativity is classified as moderate, low or very low. As for student learning outcomes there are 30 students or 100% of students who have very high learning outcomes, and there are no students or 0% of students who have high, medium, low and very low learning outcomes. From the results of inferential analysis testing using the correlation formula at the level of 95% confidence obtained rh (r count) = 0.723 consulted with table r obtained 0.361, thus rh (r count) > rt (r table) or 0.723 > 0.361. Hence the consequences Ho was rejected. Thus there is a relationship of student learning creativity with the learning outcomes of SBdP Class IV SD GPID Palu.